The THE CORRELATION BETWEEN LIPID PROFILES WITH LENGTH OF STAY AND CLINICAL OUTCOMES OF ISCHEMIC STROKE PATIENTS AT PROF. Dr. I GOESTI NGOERAH GDE NGOERAH GENERAL HOSPITAL - Indrayani, Pande Kadek Putri Rahayu; Yasa, I Wayan Putu Sutirta; Lestari, Anak Agung Wiradewi; Wande, I Nyoman (E-Jurnal Medika Udayana, 2024)
Ischemic stroke is a neurological condition due to the blockage of cerebral arteries or veins, leading to disrupted blood flow and oxygen supply to the brain. One of the causes of ischemic stroke is abnormalities in lipid profile levels. This study aims to determine the correlation between lipid profiles with the length of stay and clinical outcomes in patients with ischemic stroke. This study is cross-sectional research using secondary data from ischemic stroke patients admitted to Prof. Dr. I Goesti Ngoerah Gde Ngoerah General Hospital between January 1, 2021, and January 31, 2023, who meet the inclusion and exclusion criteria. Out of 215 study subjects included in this research, 137 (63.7%) were male, and 78 were female. Additionally, 192 (89.3%) were aged ? 45 years, and 23 (10.7%) were <45 years. Spearman's analysis showed a weak negative correlation between the length of stay and total cholesterol levels (r = 0.174, p = 0.010), LDL (r = 0.152, p = 0.026), and HDL (r = 0.141, p = 0.039), but no significant correlation was found with triglyceride levels (r = 0.020, p = 0.767). The results of this study also indicated a correlation between clinical outcomes and total cholesterol (p = 0.029) and LDL (p = 0.039), but not with triglyceride levels (p = 0.090) and HDL (p = 0.115). However, further research with a cohort method is needed to establish a direct correlation between lipid profiles with length of stay and clinical outcomes in ischemic stroke patients. Keywords : Ischemic Stroke, Length of Stay, Outcome